2017
DOI: 10.2105/ajph.2016.303605
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity and Chronic Diseases Among American Indians in Rural Oklahoma: The THRIVE Study

Abstract: Objectives To examine food insecurity and cardiovascular disease–related health outcomes among American Indians (AIs) in rural Oklahoma. Methods We surveyed a cross-sectional sample of 513 AI adults to assess food insecurity domains (i.e., food quality and quantity) and obesity, diabetes, and hypertension. Results Among AIs surveyed, 56% reported inadequate food quantity and 62% reported inadequate food quality. The unadjusted prevalence of diabetes (28.4% vs 18.4%), obesity (60.0% vs 48.3%), and hypertens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 32 publications
2
49
0
Order By: Relevance
“…A community‐based participatory research (CBPR) orientation guided this study . Our ongoing tribal‐university partnership, initiated in 2012, is steered by a committee comprising university researchers experienced in conducting CBPR and key multisector stakeholders from the Chickasaw Nation and the Choctaw Nation of Oklahoma, including representatives from tribal health promotion, nutritional and clinical services, tribal Institutional Review Boards (IRBs), and research divisions . The development of partnership processes and study methods were informed by partners’ previous CBPR with AIs in Oklahoma and elsewhere .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A community‐based participatory research (CBPR) orientation guided this study . Our ongoing tribal‐university partnership, initiated in 2012, is steered by a committee comprising university researchers experienced in conducting CBPR and key multisector stakeholders from the Chickasaw Nation and the Choctaw Nation of Oklahoma, including representatives from tribal health promotion, nutritional and clinical services, tribal Institutional Review Boards (IRBs), and research divisions . The development of partnership processes and study methods were informed by partners’ previous CBPR with AIs in Oklahoma and elsewhere .…”
Section: Methodsmentioning
confidence: 99%
“…20,21 Our ongoing tribaluniversity partnership, initiated in 2012, is steered by a committee comprising university researchers experienced in conducting CBPR and key multisector stakeholders from the Chickasaw Nation and the Choctaw Nation of Oklahoma, including representatives from tribal health promotion, nutritional and clinical services, tribal Institutional Review Boards (IRBs), and research divisions. 22,23 The development of partnership processes and study methods were informed by partners' previous CBPR with AIs in Oklahoma and elsewhere. [24][25][26][27] A unique aspect of this partnership was the participation of tribal commerce and marketing divisions, which provide economic and business expertise in creating environmental and policy interventions to promote health.…”
Section: Study Orientation and Partnershipmentioning
confidence: 99%
“…We identified seventeen peer-reviewed USA articles studying the association between FIS and diabetes (29,55,61,82,107,109,(111)(112)(113)(114)(115)(116)(137)(138)(139)(140). Of those manuscripts, twelve of them show a significant association (Table S2- patterns which may be difficult for FIS individuals (141).…”
Section: Diabetesmentioning
confidence: 99%
“…More recently, Love et al found that frequent shopping at convenience stores, gas stations, or dollar stores as regular food sources was associated with an increased prevalence of obesity and diabetes [15]. Previous studies describing Native American food environments [12,13] did not examine the relationship between the food environment and BMI, although Jernigan et al described an association between food insecurity of Native American participants and higher prevalence of obesity, diabetes, and hypertension [42]. To our knowledge, no studies have examined the association between Native American food environments and food insecurity, and this could be explored in future research.…”
Section: Discussionmentioning
confidence: 99%